2022
DOI: 10.1007/s11104-022-05714-9
|View full text |Cite
|
Sign up to set email alerts
|

Root distribution and properties of a young alley-cropping system: effects on soil carbon storage and microbial activity

Abstract: Purpose In agroforestry systems, the root distributions and properties of the annual and perennial vegetation are poorly known, although they are recognized for fostering soil carbon (C) stocks through annual root-derived C inputs and by altering microbial activity. This study aimed to evaluate the potential contribution of roots from the understory vegetation strip (UVS) and the crop to top-and subsoil C stocks (0-100 cm) to a 3-year-old agroforestry system of the alley-cropping type. Methods Root biomass, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Choosing a low sampling depth will lead to an underestimation of below-ground C storage by tree roots (Figure S1). On the other hand, the C turnover in the subsoil is poorly understood and Siegwart et al (2023) did not find a positive correlation between root C stocks and SOC for depths > 50 cm. Our results showed that the total C stock in the root system was higher up to a distance of 3.5 m compared to the grassland reference.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Choosing a low sampling depth will lead to an underestimation of below-ground C storage by tree roots (Figure S1). On the other hand, the C turnover in the subsoil is poorly understood and Siegwart et al (2023) did not find a positive correlation between root C stocks and SOC for depths > 50 cm. Our results showed that the total C stock in the root system was higher up to a distance of 3.5 m compared to the grassland reference.…”
Section: Discussionmentioning
confidence: 81%
“…However, the fine root distribution measured in our study showed that the trees allocated carbon to the subsoil via their root system. The mechanism of subsoil C storage poses many open questions (Siegwart et al, 2023) and is especially interesting for mixed cropping systems that can potentially increase C storage in soils compared to cropland. High deviations between sampling points as seen in Figure 1 have to be taken into account when interpreting the results and show that a high number of repetitions is needed for studies on complex interactions of root systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choosing a low sampling depth will lead to an underestimation of below-ground C storage by tree roots (Figure S3.2). On the other hand, the C turnover in the subsoil is poorly understood and Siegwart et al (2023) did not find a positive correlation between root C stocks and SOC for depths > 50 cm. Our results showed that the total C stock in the root system was higher up to a distance of 3.5 m compared to the grassland reference.…”
Section: Discussionmentioning
confidence: 81%
“…However, the fine root distribution measured in our study showed that the trees allocated carbon to the subsoil via their root system. The mechanism of subsoil C storage poses many open questions (Siegwart et al, 2023) and is especially interesting for mixed cropping systems that can potentially increase C storage in soils compared to cropland. High deviations between sampling points as seen in Figure 3.1 have to be taken into account when interpreting the results and show that a high number of repetitions is needed for studies on complex interactions of root systems.…”
Section: Discussionmentioning
confidence: 99%